2019
DOI: 10.1063/1.5113727
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic microscopy of poled x-cut thin film lithium niobate: Understanding the contrast mechanism

Abstract: Thin film lithium niobate is of great recent interest and an understanding of periodically poled thin-films is crucial for both fundamental physics and device developments. Second-harmonic (SH) microscopy allows for the non-invasive visualization and analysis of ferroelectric domain structures and walls. While the technique is well understood in bulk lithium niobate, SH microscopy in thin films is largely influenced by interfacial reflections and resonant enhancements, which depend on film thicknesses and the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 63 publications
0
29
0
Order By: Relevance
“…Finally, it should be noted that interfacial reflections and resonant enhancements in small structures might further influence signal strengths in SHG microscopy. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…Finally, it should be noted that interfacial reflections and resonant enhancements in small structures might further influence signal strengths in SHG microscopy. [ 51 ]…”
Section: Resultsmentioning
confidence: 99%
“…We used a diagnostic method, described in Ref. 16, to study and improve the poling process. After poling, the waveguide structure fabricated in collaboration with the University of Rochester, as reported in Ref.…”
Section: Experimental Details: Waveguide Designmentioning
confidence: 99%
“…We have recently developed a high-quality poling recipe for x-cut LNOI, and demon-strated two useful diagnostic methods using in-situ poling monitoring, and a non-destructive nonlinear microscopy technique. 15,16 This allows us to improve the poling process, and identify suitable waveguides without destroying them e.g., by cross-sectioning, and etching using dilute acids, as is typically performed in traditional poling diagnostics. In section III, we describe our experiments in performing SPDC, where we used a continuous-wave optical pump at 784.5 nm in order to generate frequencydegenerate photon pairs at 1569 nm.…”
Section: Introductionmentioning
confidence: 99%
“…[121] Among these, quasiphase matching (QPM) may be considered as the most preferred approach. [144][145][146][147][148][149] The advantages include waveguide design and optimization freedom, as well as access to the largest nonlinear coefficient of LN (d 33 ). QPM is achieved in PPLN waveguides through inverting the crystalline domain polarity periodically to compensate for the wave-vector mismatch Δk between the pump and SHG optical modes.…”
Section: Periodically Poled Tfln Waveguidesmentioning
confidence: 99%
“…More details on periodic poling of TFLN waveguides and various methods in order to study and improve domain inversion can be found in refs. [105,[144][145][146][147][148][149].…”
Section: Periodically Poled Tfln Waveguidesmentioning
confidence: 99%